2022
DOI: 10.1002/ijc.34216
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plasma phospholipid fatty acid levels and breast cancer risk in the Cancer Prevention Study‐II Nutrition Cohort

Abstract: Prospective studies that objectively measure circulating levels of fatty acids are needed to clarify their role in the etiology of breast cancer. Thirty‐eight phospholipid fatty acids were measured using gas chromatograph in the plasma fraction of blood samples collected prospectively from 2718 postmenopausal women (905 breast cancer cases) enrolled in the Cancer Prevention Study II Nutrition Cohort. Associations of 28 fatty acids that passed quality control metrics (modeled as per 1‐SD increase) with breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Most previous studies used plasma (25)(26)(27)(28)(29) or serum (30)(31)(32) n-3 PUFA as biomarkers to evaluate the association of n-3 PUFA with breast cancer risk. Although one study from plasma (28) supports our findings, most studies using plasma (25)(26)(27)29) or serum (30)(31)(32) n-3 PUFA as biomarkers reported null findings on the relationship between n-3 PUFA and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies used plasma (25)(26)(27)(28)(29) or serum (30)(31)(32) n-3 PUFA as biomarkers to evaluate the association of n-3 PUFA with breast cancer risk. Although one study from plasma (28) supports our findings, most studies using plasma (25)(26)(27)29) or serum (30)(31)(32) n-3 PUFA as biomarkers reported null findings on the relationship between n-3 PUFA and breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies used plasma (25)(26)(27)(28)(29) or serum (30)(31)(32) n-3 PUFA as biomarkers to evaluate the association of n-3 PUFA with breast cancer risk. Although one study from plasma (28) supports our findings, most studies using plasma (25)(26)(27)29) or serum (30)(31)(32) n-3 PUFA as biomarkers reported null findings on the relationship between n-3 PUFA and breast cancer risk. Compared with the plasma or serum fatty acid, the erythrocyte membrane fatty acid profile shows a longer time for fatty acid intake, approximately 4 months, and is not susceptible to the individual postprandial status (8,33) .…”
Section: Discussionmentioning
confidence: 99%
“…14 Another cohort study examining plasma phospholipid myristic acid (C14:0) found a similar positive relationship. 59 Conversely, the Nurses' Health Study reported null associations of myristic acid (C14:0), palmitic acid (C16:0), and stearic acid (C18:0) levels in erythrocyte membranes with breast cancer risk. 60 However, in line with our findings, a multicentre case-control study indicated an inverse association between serum phospholipid stearic acid (C18:0) and odds of breast cancer.…”
Section: Papermentioning
confidence: 99%
“…These modifications are essential for regulating the activity of Rho and Ras family of GTPases, which are critical for signal transduction 8,9 . Furthermore, free fatty acids (FFAs), a product of the lipogenesis pathway, play a significant role not only in normal cellular signaling but also in dysregulated pathways leading to various disorders 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Furthermore, free fatty acids (FFAs), a product of the lipogenesis pathway, play a significant role not only in normal cellular signaling but also in dysregulated pathways leading to various disorders. [10][11][12] Hypercholesterolemia is a dyslipidemic condition characterized by elevated levels of cholesterol in the bloodstream, which has abnormally high expression of the mevalonate pathway as one of the contributing factors. 13 Over the years, pharmaceutical research has led to the establishment of well-defined therapeutic approaches for this condition.…”
mentioning
confidence: 99%